1997
DOI: 10.1002/(sici)1096-9861(19971013)387:1<148::aid-cne12>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from normal and degenerating photoreceptors that two outer segment integral membrane proteins have separate transport pathways

Abstract: Detachment of the neural retina from the retinal pigment epithelium induces photoreceptor degeneration. We studied the effects of this degeneration on the localization of two photoreceptor outer segment-specific integral membrane proteins, opsin and peripherin/rds, in rod photoreceptors. Results from laser scanning confocal microscopic and electron microscopic immunolocalization demonstrate that these two proteins, normally targeted to the newly-forming discs of the outer segments, accumulate in different sub-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
53
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 52 publications
8
53
0
Order By: Relevance
“…Hence it is reasonable to infer the existence of two pools of transport vesicles, although only those vesicles bearing rhodopsin have been isolated and studied so far. The observation that peripherin/rds and rhodopsin are mislocalized in induced retinal detachment but remain segregated is consistent with this notion (Fariss et al, 1993). Some investigators have observed "cytoplasmic bridges" between the inner and outer segment (distinct from the connecting cilium), leading to the hypothesis that vesicles may bud from the apex of the inner segment to deliver components to the outer segment (Besharse and Horst, 1990).…”
Section: Transport and Localization Of Other Ros Proteins-supporting
confidence: 65%
See 2 more Smart Citations
“…Hence it is reasonable to infer the existence of two pools of transport vesicles, although only those vesicles bearing rhodopsin have been isolated and studied so far. The observation that peripherin/rds and rhodopsin are mislocalized in induced retinal detachment but remain segregated is consistent with this notion (Fariss et al, 1993). Some investigators have observed "cytoplasmic bridges" between the inner and outer segment (distinct from the connecting cilium), leading to the hypothesis that vesicles may bud from the apex of the inner segment to deliver components to the outer segment (Besharse and Horst, 1990).…”
Section: Transport and Localization Of Other Ros Proteins-supporting
confidence: 65%
“…Signal of Rhodopsin-The mislocalization of rhodopsin is involved in the pathology of various retinal degenerative diseases (Dryja et al, 1990;Fariss et al, 1993). Mutations and deletions within the distal eight amino acids of rhodopsin, later identified as the localization signal sequence, contribute to a disease cluster characterized by early onset and aggressive retinal degeneration (Sandberg et al, 1995).…”
Section: Localizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in a bright signal from the ONL in retinas detached for more than a day, with the signal increasing in extent and intensity as detachment time increases. 21 Reattachment can stop this process; treatment with BDNF or hyperoxia can diminish it. 3,8 When the retina is reattached after 1 h of detachment there is almost no redistribution (Figure 5c).…”
Section: Rod Opsin Redistributionmentioning
confidence: 99%
“…An additional role in the proper positioning or anchoring of cellular organelles is implicated by the association of photoreceptor rootlets with membranebound saccules, endoplasmic reticulum (ER), Golgi membranes, and mitochondria (19,24). Finally, a role for rootlets in intracellular protein transport has also been suggested (4). Provision of structural support, organization of cellular organelles and participation in intracellular trafficking seem plausible hypotheses, but none was tested directly.…”
mentioning
confidence: 99%